(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India‘s maritime domain is very vast. It stretches from the Persian Gulf to the Malacca Straits, and to the down south in the Indian Ocean. The maritime domain of India is defined by its diverse interests, which stretch out in the respective maritime region with its various maritime installations, economic area of interest and the security and protection of the major assets around the maritime borders.